I-1-deficiency negatively impacts survival in a cardiomyopathy mouse model. (1st September 2015) - Friedrich, Felix W.; Sotoud, Hannieh; Geertz, Birgit; Weber, Silvio; Flenner, Frederik; Reischmann, Silke; Eschenhagen, Thomas; Carrier, Lucie; El-Armouche, Ali
Abstract: Aims: Hypertrophic cardiomyopathy (HCM) is characterized by left ventricular hypertrophy, diastolic dysfunction and increased interstitial fibrosis. Current treatment is based on beta-adrenoceptor (AR) and calcium channel blockers. Since mice deficient of protein phosphatase-1 inhibitor-1 (I-1), an amplifier in beta-AR signalling, were protected from pathological adrenergic stimulation in vivo, we hypothesized that I-1 ablation could result in an improved outcome in a HCM mouse model. Methods and results: We crossed mice deficient of I-1 with homozygous myosin-binding protein C knock-out ( Mybpc3 KO) mice exhibiting cardiac dilatation and reduced survival. Unexpectedly, survival time was shorter in double I-1 / Mybpc3 KO than in single Mybpc3 KO mice. Longitudinal echocardiographic assessment revealed lower fractional area change, and higher diastolic left ventricular inner dimensions and end-diastolic volumes in Mybpc3 KO than in WT mice. In comparison to Mybpc3 KO, double I-1 / Mybpc3 KO presented higher left ventricular end-diastolic volumes, inner dimensions and ventricular surface areas with increasing differences over time. Phosphorylation levels of PKA-downstream targets and mRNA levels of hypertrophic markers did not differ between I-1 / Mybpc3 KO and single Mybpc3 KO mice, except a trend towards higher beta-myosin heavy chain levels in double I-1 / Mybpc3 KO. Conclusion: The data indicate that interference with beta-AR signalling has no long-term benefit in this severe MYBPC3 -related cardiomyopathy mouse model.